A Mobile Remote Lab System to Monitor in Situ Thermal Solar Installations - Saez de Arregui, Gastón; Plano, Miguel; Lerro, Federico; Petrocelli, Lucía; Marchisio, Susana; Concari, Sonia; Scotta, Virginia (International Journal of Interactive Mobile Technologies (iJIM), 2013)
In this paper we describe the design and development of interconnected devices which allow monitoring in situ the performance of solar boilers. This mobile remote lab system comprises two huge blocks of hardware: a mobile station located by the boiler, which is monitored and controlled in a remote way, and a fixed station, located in the Laboratory of Energy for the Sustained Development of the Universidad Nacional de Rosario. The communication between the fixed and mobile devices is controlled by microcontrollers included in both stations and programmed in C language. The project is being developed through three parallel lines of work: 1) Design and development of fixed and mobile hardware; 2) Development of firmware and software necessary to register and communicate data; 3) Design and development of learning activities. This mobile remote lab will be useful to test the behavior of solar boilers in the place and environmental conditions where they are placed so as to evaluate their performance and efficiency anywhere. This is also in order to contribute for the implementation of norms for the certification of solar boilers. On the other hand, the data and results obtained from the development will be used as supplies for the design of learning activities